Efektivitas Edukasi Kesehatan Terhadap Perilaku Hidup Bersih Dan Sehat Pada Masyarakat: Studi Literatur - Fitri Fitri; Sri Endang Sari; Fuji Lestari; Dwita Nazil A (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Public awareness in Indonesia regarding the implementation of Clean and Healthy Living Behavior (Perilaku Hidup Bersih dan Sehat/PHBS) remains considerably low, necessitating structured and continuous educational interventions as a strategic solution. This study aims to analyze and synthesize scientific evidence on the effectiveness of health education toward PHBS transformation in communities. The method employed was library research with a qualitative approach through systematic literature review, utilizing Google Scholar, Garuda, and Portal Sinta databases with inclusion criteria of articles published between 2021 and 2025. Content analysis was applied to all literature meeting the selection criteria. The findings consistently demonstrate that health education programs are capable of enhancing knowledge, shifting attitudes, and promoting concrete PHBS practices, evidenced by p-values below 0.05 across various reviewed studies. The most effective methods encompass combinations of the PRECEDE-PROCEED model, Health Belief Model, advocacy strategies, and community empowerment integrated with local wisdom. Key success factors include media quality, material relevance, approach creativity, program consistency, social support, and the target population's health literacy level. It is concluded that the effectiveness of health education toward PHBS is multidimensional and highly dependent on the alignment between methods, sociocultural contexts, and the sustainability of applied intervention programs.